2020
DOI: 10.1002/agj2.20231
|View full text |Cite
|
Sign up to set email alerts
|

Carbon accumulation of cool season sports turfgrass species in distinctive soil layers

Abstract: Carbon sequestered by turfgrasses may contribute to reducing atmospheric CO 2 levels, to improved soil health, and to increased turfgrass quality. The objective of this study is to compare the amount of soil C accumulated by nine cool season turfgrass monocultures and 12 mixtures of turfgrass species during the first 3 yr of establishment. Thatch, mat, and other soil layers were sampled and thickness of these layers was quantified in a field study conducted in the Netherlands. From these samples, dry matter, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Thatch in turfgrass has been defined as a layer of dead and living stems and roots that accumulates faster than decomposition between the green vegetation and the soil surface [ 45 ]. A study in 2020 reported that thatch built up rapidly after turfgrass establishment and contributed to carbon accumulation in turfgrass systems [ 46 ]. Turfgrass thatch layers have a higher carbon concentration (due to a higher lignin content) than verdure, roots, and underlying soils [ 47 , 48 ].…”
Section: Turfgrass Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thatch in turfgrass has been defined as a layer of dead and living stems and roots that accumulates faster than decomposition between the green vegetation and the soil surface [ 45 ]. A study in 2020 reported that thatch built up rapidly after turfgrass establishment and contributed to carbon accumulation in turfgrass systems [ 46 ]. Turfgrass thatch layers have a higher carbon concentration (due to a higher lignin content) than verdure, roots, and underlying soils [ 47 , 48 ].…”
Section: Turfgrass Systemsmentioning
confidence: 99%
“…Turfgrass thatch layers have a higher carbon concentration (due to a higher lignin content) than verdure, roots, and underlying soils [ 47 , 48 ]. Therefore, thatch is a potential carbon pool in turfgrass systems [ 39 , 46 , 47 ].…”
Section: Turfgrass Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 26 manuscripts were submitted to Agronomy Journal , of which 15 were accepted for publication after the peer review process. Topics covered in this issue include turfgrass morphology (Pease, Thoms, Arora, & Christians, 2020), sod production (Griffith et al., 2020), turfgrass performance affected by management approaches (Dalsgaard, Thoms, Christians, Mertz, & Horton, 2020; Miller & Brotherton, 2020; Schiavon, Mock, Stowell, & Baird, 2020), and carbon accumulation in rootzone layers (Evers, de Kroon, Visser, & de Caluwe, 2020). Topics also include the effect of fertilization on establishment (Lindsey, Thoms, & Christians, 2020; Øgaard & Aamlid, 2020) and maintenance strategies for disease control (Hempfling, Murphy, & Clarke, 2020; Mattox et al., 2020; Mattox, Kowalewski, & McDonald, 2020; Mattox, Kowalewski, McDonald, Lambrinos, & Pscheidt, 2020).…”
mentioning
confidence: 99%